Effects of modified Danggui Sini Decoction as adjuvant therapy for angina pectoris in coronary heart disease: a systematic review and meta-analysis based on randomised controlled trials - Wang, He; Liu, Changxing; Guo, Xinyi; Yang, Jianfei; Zhou, Yabin (Frontiers in Pharmacology, 2024)
Introduction: This systematic review evaluates the efficacy of the Chinese herbal formula modify Danggui Sini Decoction as an adjunctive treatment for angina pectoris in patients with coronary heart disease. Methods: We conducted a comprehensive search for randomized controlled trials (RCTs) that investigated the effects of modify Danggui Sini Decoction in combination with conventional Western medication on angina pectoris in coronary artery disease, published up to July 2023 across eight databases, including China Knowledge International (CNKI). Literature screening and data extraction were performed by two researchers following predefined inclusion and exclusion criteria. The quality of included studies was assessed using the Cochrane Handbook version 5.1, and meta-analysis was executed via RevMan 5.4 software. Results: Thirteen studies encompassing 1,232 participants were incorporated. The meta-analysis revealed that combining modify Danggui Sini Decoction with conventional Western medication significantly enhanced overall clinical efficacy, reduced the duration of angina attacks, decreased the Chinese medicine syndrome score, improved inflammatory markers and cardiac function, lowered serum NT-proBNP levels, and elevated the Seattle Angina Questionnaire (SAQ) scores compared to the control group. Conclusion: modify Danggui Sini Decoction, when used alongside conventional Western medications, shows promise in treating coronary artery disease patients with angina pectoris and may serve as a beneficial adjunctive therapy in clinical settings. Nonetheless, due to the limited quantity and quality of the included studies, further high-caliber research is essential to substantiate these findings.